PENGARUH KESADARAN WAJIB PAJAK TERHADAP EFEKTIFITAS PEMUNGUTAN PAJAK - Rustan Rustan; Mira Mira (Universitas Muhammadiyah Makassar, 2018)
This research aims to determine the effect of taxpayer awareness on the effectiveness of tax voting in Makassar region in 2016, population of this research is KPP Pratama Makassar South District Office of Regional Directorate Regional tax general of Makassar. The number of samples spread out by 50 but returned as many as 32 people willing to become respondents. The data analysis technique used in this study is a multiple linear regression analysis. The results of this study showed that the taxpayer awareness (X1) has a significant effect on the effectiveness of the tax poll where the value of the calculated T is 0,028 < 0.05 (5%).